The Influence of Digital Financial Services, Social Media, and Buy Now Pay Later on Over-Indebtedness with Financial Literacy as a Moderating Variable - Helma Yuliyana; Abdul Mukti Soma (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study investigates the impact of digital financial services and financial literacy on the issue of over-indebtedness among Millennials and Generation Z in Jakarta. Utilizing a quantitative approach with a causal design, data were gathered from 254 participants through questionnaires and analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM). Findings reveal that both digital financial services and financial literacy significantly influence over-indebtedness. Notably, higher levels of over-indebtedness correspond to more effective debt management and reduced financial distress. This suggests that leveraging digital financial services, alongside enhanced financial literacy, fosters improved financial stability in younger demographics. In contrast, social media and Buy Now Pay Later options did not demonstrate significant effects, and financial literacy did not serve as a moderating factor in the examined relationships. This research enriches the understanding of youth financial behavior within the digital economy and offers actionable insights for promoting financial literacy and risk management strategies aimed at sustaining financial well-being among Millennials and Generation Z.